(untitled) (Panacea Journal of Medical Sciences, 2020)
Prehypertension is associated with excessive morbidity and mortality due to Cardiovascular diseases (CVD). Our study emphasizes the need of early diagnosis of left ventricular diastolic dysfunction in prehypertension patients and to perform echocardiogram in prehypertension middle aged patients. Materials and Methods: Its hospital based cross sectional study done on 50 samples all middle aged patients of both sexes with prehypertension in the age group of 45-64years. Results: The mean E value was found to be 69.78+4.83, mean value of A was 68.88+5.71 and mean value of E/A 1.01+.0.15. About 17(34%) had normal diastolic function E/A Ratio between 1.0-1.5 and 33 (66%) had impaired relaxation grade 1. There is no significant difference between the smokers and non – smokers, likewise for obese and non -obese patients. Conclusion: We conclude that even non obese patients and non- smokers has significant diastolic dysfunction, so prehypertension is risk factor for diastolic dysfunction.